Traffic as a Source of Organophosphorus Flame Retardants and Plasticizers in Snow - Marklund, Anneli; Andersson, Barbro; Haglund, Peter (Environmental science & technology, 2005)
Snow samples collected in northern Sweden at a road intersection and an airport indicated that traffic is a source of organophosphorus flame retardants and plasticizers (OPs) in the outdoor environment. Analysis of snow samples taken at distances of 2, 100, and 250 m from the road intersection showed that the total amount of OPs declined as distance increased. Of the 11 analyzed substances, tris(2-chloroisopropyl) phosphate (TCPP) dominated in the snow samples from the intersection, with levels of 170, 130, and 110 ng/kg snow at distances of 2, 100, and 250 m. Similar amounts of TCPP were found at the airport (100−220 ng/kg). These levels are approximately twice as high as the level found in the reference snow sample from a remote area (70 ng/kg). A possible explanation for the higher levels of TCPP found close to the road intersection is that it may be emitted from the interior of cars via their ventilation systems. Triphenyl phosphate (TPP) was identified in lubricants and in waste oil from vehicles, and thus, leakage of transmission and motor oils is a probable source of TPP found at the sampled sites. Ten OPs were detected in the three samples from the airport, of which tributyl phosphate (TBP) was the most abundant, at levels 3 orders of magnitude higher than in the reference sample, that is, 25 000 compared to 19 ng/kg. The main source of TBP at the airport was traced to aircraft hydraulic fluid. Analysis of background air and deposition samples indicated that some OPs are subject to long-range air transportation.